Vibration suppression of sprayer boom structure using active torque control and iterative learning. Part II: Experimental implementation. (October 2018) - Tahmasebi, Mona; Gohari, Mohammad; Mailah, Musa; Abd Rahman, Roslan
The most common technique of protecting crops from diseases is by applying a chemical process whereby a mixture of chemicals and water are sprayed onto the crops via a sprayer. Nowadays, modern sprayers are generally implemented to suspension systems for reducing the unwanted vibration of the spray boom structure to improve the uniformity of spray distribution in the agricultural field environment. This paper serves to present a new alternative to address and resolve the vibration control problem of the moving sprayer structures. The application of an active torque control (ATC) method to cancel the undesired vibration of the sprayer boom is thus proposed. As a continuation from Part I that deals with the modeling and simulation aspect, Part II explains the practical facet of the study through the implementation of ATC and iterative learning (ATCAIL) control scheme to an experimental spray boom structure as a basis to validate the effectiveness and robustness of the scheme as simulated and described at length in Part I. A sprayer boom suspension system test rig was specifically designed and developed to verify this control scheme that was principally chosen due to its ease of implementation through the exploitation of simple proportional–integral–derivative (PID), ATC and iterative learning algorithms. The system performance was evaluated and compared to the PID and ATC–PID control schemes for benchmarking. The results demonstrate the capability of the practical ATCAIL scheme to improve the vibration suppression in both time and frequency domains, thereafter guaranteeing a more uniform spray distribution of chemicals on a bumpy terrain. The experimental outcomes are in good agreements with the simulation counterpart.